2017
DOI: 10.5194/bg-14-5239-2017
|View full text |Cite
|
Sign up to set email alerts
|

How big is the influence of biogenic silicon pools on short-term changes in water-soluble silicon in soils? Implications from a study of a 10-year-old soil–plant system

Abstract: Abstract. The significance of biogenic silicon (BSi) pools as a key factor for the control of Si fluxes from terrestrial to aquatic ecosystems has been recognized for decades. However, while most research has been focused on phytogenic Si pools, knowledge of other BSi pools is still limited. We hypothesized that different BSi pools influence short-term changes in the water-soluble Si fraction in soils to different extents. To test our hypothesis we took plant (Calamagrostis epigejos, Phragmites australis) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 61 publications
(78 reference statements)
1
36
0
Order By: Relevance
“…Several cultivated plants are high Si‐accumulators. In particular, monocotyledons, notably cereals and sugarcane, actively take up dissolved silica (Deshmukh & Bélanger, ) which precipitates in plant tissues as amorphous silica bodies named phytolith (McKeague & Cline, ), a phytogenic silica (PhSi; Cooke & Leishman, ; McKeague & Cline, ; Puppe et al, ; Sommer et al, ). Once deposited into soil within organic debris, phytoliths can dissolve and provide plant‐available Si (McKeague & Cline, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several cultivated plants are high Si‐accumulators. In particular, monocotyledons, notably cereals and sugarcane, actively take up dissolved silica (Deshmukh & Bélanger, ) which precipitates in plant tissues as amorphous silica bodies named phytolith (McKeague & Cline, ), a phytogenic silica (PhSi; Cooke & Leishman, ; McKeague & Cline, ; Puppe et al, ; Sommer et al, ). Once deposited into soil within organic debris, phytoliths can dissolve and provide plant‐available Si (McKeague & Cline, ).…”
Section: Introductionmentioning
confidence: 99%
“…Silica in plants is an important component of the silicon geochemical cycle because it is more available than silicon originating from minerals (Derry et al 2005;Fraysse et al 2009;Puppe et al 2017). The influence of phytolith biogenic silica content on ecosystems was shown by several authors (Wang et al 2011;Ran et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on the dissolution behavior of phytoliths in plant tissues. Puppe et al (2017), however, reported that a silicon pool evolves through release of silicon in soils, because phytogenic Si in plant tissues is temporarily protected from dissolution. Studying dissolution of phytoliths in tissues may enable more accurate estimates of the amount of dissolved silicon from fossil and subfossil needles, and provide a better understanding of phytolith taphonomy.…”
Section: Introductionmentioning
confidence: 99%
“…a silica ring formed around the periphery of the cell, deposited on a dispersed organic matrix, or laid down as deposits within the cell wall or between the cellulose wall and the plasma membrane or in cortical intercellular spaces within the cell (Prychid et al, 2003). In general, these fragile phytogenic silica structures as well as very small phytoliths (<5 µm) are difficult to trace in sediments, but they potentially play an important role in silica cycling (Meunier et al, 2017;Puppe et al, 2017). Additionally, given the very large number of epiphytic diatoms on non-rinsed plant samples, it cannot be excluded that a fraction of plant-silica in our results is actually diatom-silica, even though plants were washed thoroughly before analysis, according to protocol.…”
Section: The Role Of Macrophytes and Diatoms In Lagoon Bsi Storagementioning
confidence: 99%
“…Struyf et al, 2015). Alternatively, Puppe et al (2017) suggest the formation of a layer of coarse organic matter on top of sediments from which phytoliths cannot be released easily and hence are missing in underneath sediment layers. We have no arguments supporting either of these hypotheses, none of our sediment cores contained such a distinct organic top layer and samples were visually homogeneous organic rich (fine material) over the entire depth of the core (15 cm).…”
Section: The Role Of Macrophytes and Diatoms In Lagoon Bsi Storagementioning
confidence: 99%